A newly identified NLR-like gene participates in bacteria and virus infection possibly through regulating hemocytes apoptosis in shrimp. (July 2022) - Li, Xuechun; Li, Shihao; Sun, Mingzhe; Yu, Yang; Zhang, Xiaojun; Xiang, Jianhai; Li, Fuhua
Abstract: The nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) play important roles in innate immunity. Previously, we identified an NLR -like gene, LvNLRPL1, and found that it participated in Vibrio infection and regulated hemocytes apoptosis in the Pacific whiteleg shrimp Litopenaeus vannamei . However, it is still unclear whether other NLR -like genes exist in shrimp and how they function during virus infection. In the present study, a novel NLR -like gene ( LvNLRPL2 ) was identified and functionally characterized in L. vannamei . LvNLRPL2 was highly expressed in hemocytes and responsive to both Vibrio parahaemolyticus and white spot syndrome virus (WSSV) infection. Knockdown of LvNLRPL2 could markedly increase the proliferation of Vibrio and the mortality of shrimp infected with V. parahaemolyticus, whereas inhibit in vivo WSSV propagation in shrimp, indicating its distinct roles during Vibrio and WSSV infection. After LvNLRPL2 knockdown, the apoptotic rate of hemocytes increased, and the expression levels of LvCaspase 2, 3 and 5 were significantly up-regulated. In addition, LvNLRPL2 could form a hetero-dimer with LvNLRPL1 through their NACHT domains. These results suggest that LvNLRPL2 might resist bacterial infection while promote WSSV propagation by forming hetero-dimer with LvNLRPL1 and then inhibiting apoptosis of hemocytes. These data will be helpful for understanding the functions of NLR -like genes and their regulation mechanisms in crustaceans. Highlights: LvNLRPL2 is responsive to Vibrio and WSSV infection in Litopenaeus vannamei. Knockdown of LvNLRPL2 increases the proliferation of Vibrio and the mortality of shrimp infected with V. parahaemolyticus. Knockdown of LvNLRPL2 inhibits in vivo WSSV propagation in shrimp. Knockdown of LvNLRPL2 up-regulates expression of Caspase 2, 3 and 5 in hemocytes and increases hemocytes apoptosis. LvNLRPL2 could form a hetero-dimer with LvNLRPL1 through their NACHT domains.